Speech Acts in Emma Watson’s Interview with People/Entertainment Weekly Network (PEN) - Reychelin Lea Jawar (Institute of Research and Community Outreach - Petra Christian University, 2026)
Speech acts are very important in daily conversation. In this study, the writer analyzes Emma Watson’s speech acts in the interview with People/Entertainment Weekly Network (PEN). The analysis used speech acts theory by Searle (1969, as cited in Yule, 1996). The writer found that the speaker only used three types of speech acts, which are representatives, expressives, and commissives. The writer found that the most frequently used type of speech acts were representatives. The writer did not find the declarations and directives types in Emma's speech since Emma did not have the authority or some kind of institutional role to be able to affect and change a certain condition through her utterances. In the interview, she also did not need help that required her to order someone to do something for her. Therefore, the writer found that the most frequently used type of speech acts were representatives.